Iron bioavailability of a casein-based iron fortificant compared with that of ferrous sulfate in whole milk: a randomized trial with a crossover design in adult women. Issue 6 (1st October 2019) - Henare, Sharon J; Nur Singh, Nadia; Ellis, Ashling M; Moughan, Paul J; Thompson, Abby K; Walczyk, Thomas
ABSTRACT: Background: A highly soluble iron–casein complex has been developed for food fortification purposes with the aim to provide high iron bioavailability. Objective: We aimed to determine the iron bioavailability of the iron–casein complex relative to that of ferrous sulfate (control) when given with whole milk in healthy young women. Methods: A randomized comparator-controlled trial with a crossover design was conducted using the erythrocyte incorporation dual stable isotope ( 57 Fe, 58 Fe) technique. Iron absorption from the iron–casein complex was compared with that from ferrous sulfate in 21 healthy women aged 20–38 y with normal iron status. Results: Fractional iron absorption (geometric mean; −SD, +SD) from the iron–casein complex (3.4%; 1.4%, 5.4%) and from ferrous sulfate (3.9%; 1.7%, 6.1%) were not statistically different ( P > 0.05). The relative bioavailability value of the iron–casein complex to ferrous sulfate was determined to be 0.87 (−1 SD, +1 SD: −0.90, +2.64). Conclusions: The iron–casein complex has iron bioavailability comparable to that of ferrous sulfate in healthy young women. This trial was registered at www.anzctr.org.au as ACTRN12615000690550.